METODOLOGI GROUNDED THEORY - Adibah, Ida Zahara (Fakultas Agama Islam UNDARIS, 2018)
ABSTRACTGrounded theory was first introduced by Glasser and Strauss in The Discovery of Grounded Theory (1967). The main purpose, first rationalizing the theory that is grounded, processed and developed by data processing activities during the research process takes place. According to Glaser and Strauus, this type of theory